Compliance with COVID-19 health protocols in a restricted offline learning setting in Palembang, Indonesia: a structural equation modeling - Fitrianto, Mohammad Eko; Nofiawaty; Wahab, Zakaria; Hanafi, Agustina (Public Health and Preventive Medicine Archive, 2024)
Background and purpose: The COVID-19 pandemic has brought about new-normal conditions across all sectors. At the onset of the return to offline learning, new health protocol regulations were introduced. This study aimed to predict student behaviour in the post-COVID-19 learning process using the Health Belief Model (HBM) within a restricted face-to-face learning context.  Methods: This cross-sectional survey involved 331 students from both public and private universities in South Sumatra Province, selected through convenience sampling from those participating in post-pandemic face-to-face learning. Data were collected between April and July 2022 using an online questionnaire that covered sociodemographic characteristics and perceptions based on the HBM framework. Descriptive analysis was conducted, and behavioural predictions were tested using Structural Equation Modelling (SEM).  Results: The majority of participants were female (54.4%), aged 18–21 years (64.4%), predominantly undergraduate students (84%), and residing in Palembang (63.3%). Regarding vaccination status, 54.4% had received the second dose, 39% the third dose, 5.7% only the first dose, and 0.9% were unvaccinated. Perceived benefits (β=0.129, p=0.034), cues to action (β=0.319, p<0.001), and self-efficacy (β=0.442, p<0.001) were found to be significant predictors of students’ compliance with health protocols.  Conclusion: Students’ compliance with health protocols is influenced by health-related information and their level of self-efficacy. The Health Belief Model proves effective in predicting this behaviour in a post-COVID-19 context. Policymakers are encouraged to promote compliance to health protocols through positive messaging, such as public service announcements.